Geology and geochemistry of Middle Eocene Maden complex ferromanganese deposits from the Elazığ–Malatya region, eastern Turkey - Şaşmaz, Ahmet; Türkyılmaz, Bayram; Öztürk, Nevin; Yavuz, Fuat; Kumral, Mustafa (My University, 2014)
In the study region, the Pütürge Precambrian–Permian metamorphic rocks, the Upper Jurassic–Lower Cretaceous Guleman ophiolites, the Upper Cretaceous–Lower Eocene Hazar unit, the Campanian–Lower Maastrichtian aged Elazığ magmatics, and the Middle Eocene Maden complex crop out extensively. The Maden complex containing ferromanganese mineralization unconformably overlies the Pütürge metamorphic rocks, the Guleman ophiolites, and the Hazar unit and is unconformably overlain by Plio–Quaternary sediments. The ferromanganese (Mn–Fe) ores in the Elazığ–Malatya region, eastern Turkey, are hosted in the mudstone member of the volcano-sedimentary part of the Middle Eocene Maden complex as lenses or interbedded layers. In the Elazığ–Malatya region, Mn–Fe ores occur at eight localities, namely, Beyhan, Palu, Sarıkamış, Koçkale, Germili, Hazar, Alihan, and Kom. Mn–Fe ores are found in the Koçkale and Palu deposits as a single bed but in the Hazar and Kom deposits as two beds and in the Sarıkamış, Germili, and Alihan deposits in three levels. The thickness of these mineralized levels ranges from 0.3 m to 10 m. All the investigated mineralizations are conformable with the foot wall mudstones. Braunite, bixbyite, jacobsite, pyrolusite, manganite, and psilomelane are the main manganese oxide minerals. Hematite, barite, and pyrite are also found in variable amounts in the ferromanganese ores. The trace element content of all studied ferromanganese deposits is generally in low concentrations and tends to enrichment in the assemblage of Ba, Sr, V, Cu, Pb, Zn, and As with a geochemical characteristic similar to hydrothermal deposits. Rare earth element (REE) patterns of the Maden complex Mn–Fe deposits support a hydrothermal origin, with a slight enrichment in the middle REE (4.04–29.91 ppm, average = 16.49) and a slightly high concentration of total REE (92.40–738.23 ppm, average = 517.85). In all the investigated deposits, REE patterns displayed negative Ce (0.08 to 0.72, average = 0.15) and Eu (0.55 to 0.82, average = 0.72) anomalies. This shows that low-temperature hydrothermal fluids played an important role in the formation of mineralization. The ore deposition is similar to that of sedimentary-exhalative mineralization, deposited within the Maden marginal basin.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Mn–Fe deposits; REE chemistry; Elazığ–Malatya; Turkey